Predictive analytics using Rattle and Qlik sense : create comprehensive solutions for predictive analysis using Rattle and share them with Qlik Sense /: create comprehensive solutions for predictive analysis using Rattle and share them with Qlik Sense. (2015) - Pagans, Ferran Garcia
No abstract available